2020
DOI: 10.1093/mnras/staa628
|View full text |Cite
|
Sign up to set email alerts
|

Venturing beyond the ISCO: detecting X-ray emission from the plunging regions around black holes

Abstract: We explore how X-ray reverberation around black holes may reveal the presence of the innermost stable circular orbit (ISCO), predicted by General Relativity, and probe the dynamics of the plunging region between the ISCO and the event horizon. Being able to directly detect the presence of the ISCO and probe the dynamics of material plunging through the event horizon represents a unique test of general relativity in the strong field regime. X-ray reverberation off of the accretion disc and material in the plung… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…In such a case, the Comptonized photons from the corona should generate a reflection 9 component. However, the gas is highly ionized in the plunging region (Reynolds & Begelman 1997;Wilkins et al 2020). The impact of such radiation on the estimate of the Johannsen deformation parameter α 13 was studied in , where it was shown that for fast-rotating black holes associated with very small plunging regions (which is the case of the sources presented in our study) the impact is negligible for present and near future X-ray data.…”
Section: Discussionmentioning
confidence: 78%
“…In such a case, the Comptonized photons from the corona should generate a reflection 9 component. However, the gas is highly ionized in the plunging region (Reynolds & Begelman 1997;Wilkins et al 2020). The impact of such radiation on the estimate of the Johannsen deformation parameter α 13 was studied in , where it was shown that for fast-rotating black holes associated with very small plunging regions (which is the case of the sources presented in our study) the impact is negligible for present and near future X-ray data.…”
Section: Discussionmentioning
confidence: 78%
“…The passage of photons in the curved space-time around the black hole was followed using General Relativistic ray-tracing simulations. Rays were traced by integrating the null geodesic equations in the Kerr space-time using the CUDAKERR GPU-based ray-tracing code (Wilkins & Fabian 2012Wilkins et al 2016;Wilkins, Reynolds & Fabian 2020).…”
Section: T R Ac I N G T H E R E T U R N I N G R a D I At I O Nmentioning
confidence: 99%
“…The extension of the decaying tail of the response function, however, is encoded in the higher frequency Fourier components (Wilkins et al 2020). The delayed, scattered photons from the inner disc lead to a steepening of the decay of the time lag at high frequencies.…”
Section: Lag-frequency Spectramentioning
confidence: 99%
“…The plunging region can thus generate a reflection spectrum. However, the gas in the plunging region is highly ionized (Reynolds & Begelman 1997, Wilkins et al 2020a) and therefore its spectrum looks like a power-law component: even if we employ a relativistic reflection model that ignores the reflection from the plunging region, the impact on the measurements of the model parameters is often modest (Cardenas-Avendano et al 2020).…”
Section: Disk Structurementioning
confidence: 99%